2020
DOI: 10.1002/jcp.29535
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional memory in skeletal muscle. Don't forget (to) exercise

Abstract: Transcriptional memory describes an ancient and highly conserved form of cellular learning that enables cells to benefit from recent experience by retaining a mitotically inheritable but reversible memory of the initial transcriptional response when encountering an environmental or physiological stimulus. Herein, we will review recent progress made in the understanding of how cells can make use of diverse constituents of the epigenetic toolbox to retain a transcriptional memory of past states and perturbations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 149 publications
0
14
0
1
Order By: Relevance
“…Notably, PRMTs are also involved in arginine methylation of histones 19 , and the GO enrichment analyses thus collectively suggest differential methylation of speci c histone amino acid residues just after exercise. These results may aid future research in identifying more targeted approaches in studying the role of epigenetic modi cations in SkM during exercise 29,33,34 , and we note that differential expression largely involved histone methyltransferases and not DNA methyltransferases.…”
Section: Discussionmentioning
confidence: 71%
“…Notably, PRMTs are also involved in arginine methylation of histones 19 , and the GO enrichment analyses thus collectively suggest differential methylation of speci c histone amino acid residues just after exercise. These results may aid future research in identifying more targeted approaches in studying the role of epigenetic modi cations in SkM during exercise 29,33,34 , and we note that differential expression largely involved histone methyltransferases and not DNA methyltransferases.…”
Section: Discussionmentioning
confidence: 71%
“…CpG islands mainly co-localize with promoters and transcription start sites. Unlike the vast majority of CpGs located in the intergenic regions and repetitive elements, CpG islands are typically unmethylated regardless of the transcriptional activity of a neighboring genebut if they become hypermethylated, they promote gene silencing [23]. While CpG methylation at transcription start sites is generally associated with gene silencing, recent studies have shown that DNA methylationif it is in the gene bodymay be positively correlated with gene transcription and have its impact on the occurrence of alternative splicing [24].…”
Section: Epigeneticsmentioning
confidence: 99%
“…Conversely, deacetylation of histones correlates with transcriptional silencing and the heterochromatic state [21]. Not only does histone acetylation facilitate destabilization of DNA-nucleosome interactions for active transcription, but-when provoked on a global scale-it promotes rearrangements in the three-dimensional genome architecture, thus enabling extensive translocation of genomic loci and regulatory regions to a nuclear pore complex [23,33]. Some epigenetic modifications directly affect the cognitive functions of the body and are associated with better results in learning tests and a better memory [34] for example with the very phenomenon of histone acetylation that is directly related to active transcription and the establishment of a long-term memory [35].…”
Section: Epigeneticsmentioning
confidence: 99%
“…Epigenetics is defined as non-sequence structural modifications of DNA and/ or histones that alter patterns of gene expression, and diverse environmental stimuli can provoke epigenetic responses in many different cell types that can last for decades, and even be transferred to offspring, one example being maternal nutritional status (Vineis et al, 2017). Current evidence also supports a long-lasting exercise-induced epigenetic memory in skeletal muscle (Beiter et al, 2020), whereby previous strength training, leading to long-lasting changes in DNA methylation patterns, aided future muscle mass gains in humans. Thus, all environmental stimuli that can lead to shortterm cellular adaptation can lead to epigenetic imprinting that bear the potential of a longterm cellular memory.…”
Section: University Of Oslo Norwaymentioning
confidence: 99%